2020
DOI: 10.3389/fnint.2020.556839
|View full text |Cite
|
Sign up to set email alerts
|

Deep rTMS Mitigates Behavioral and Neuropathologic Anomalies in Cuprizone-Exposed Mice Through Reducing Microglial Proinflammatory Cytokines

Abstract: In comparison to conventional repetitive transcranial magnetic stimulation (rTMS), theta burst stimulation is stronger and more effective as a brain stimulation approach within short periods. Although this deep rTMS technique is being applied in treating neuropsychiatric disorders, few animal studies have attempted to clarify the neurobiological mechanisms underlying its beneficial effects. This animal study examined the effects of deep rTMS on the cuprizone-induced neuropathologic and behavioral anomalies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Previous findings have shown that rTMS may suppress or induce glial activation via different frequency and strength used and may be context-dependent. For example, rTMS treatment (gamma oscillations, 30-40 Hz) for 4 weeks has been reported to attenuate cuprizone-induced microglia activation and pro-inflammatory cytokine expression in the frontal cortex and hippocampus of the affected mouse brains [ 68 ]. In a rat model of spinal cord injury, high frequency (25 Hz) rTMS treatment for 8 weeks was found to suppress astrocyte activation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings have shown that rTMS may suppress or induce glial activation via different frequency and strength used and may be context-dependent. For example, rTMS treatment (gamma oscillations, 30-40 Hz) for 4 weeks has been reported to attenuate cuprizone-induced microglia activation and pro-inflammatory cytokine expression in the frontal cortex and hippocampus of the affected mouse brains [ 68 ]. In a rat model of spinal cord injury, high frequency (25 Hz) rTMS treatment for 8 weeks was found to suppress astrocyte activation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…rTMS has been shown to alter IL-10 levels in a variety of situations. rTMS reduced the activation of microglia and increased the level of IL-10 in the cortex, alleviating neurological abnormalities in rats with MS-induced neurological injury ( Yang et al, 2020 ). The reduction of neurotoxic astrocyte polarization through IL-10 effects has been proposed as a mechanism by which rTMS (5-10 Hz) is effective in nerve regeneration induced by stroke in rats ( Hong et al, 2020 ).…”
Section: Repetitive Transcranial Magnetic Stimulation For Central Neu...mentioning
confidence: 99%
“…Interestingly, ziprasidone (an antipsychotic medication approved for the treatment of schizophrenia and also considered to possess the least risk of weight gain [91]) also increased the translocation of Nrf2 from the cytoplasm to the nucleus [92], suggesting that this shared mechanism with rTMS could be responsible for its relatively low liability for weight gain in patients. Theoretically, rTMS could also potentially be anti-inflammatory via its effect on glial cells, since high frequency rTMS was shown to inhibit the proliferation of astrocytes and reduced microglial activation in rodent CNS [93,94]; reactive astrocytes and activated microglia can contribute to neuroinflammation and neuronal death [95] and have been implicated in the pathophysiology of schizophrenia [96].…”
Section: Anti-inflammatory Effect Of Rtmsmentioning
confidence: 99%